Hacking As A Challenge for Change and The Development of Cyber Law in Indonesia - Putra, Jay Sadikin Abdul Azis Mandala (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2023)
This research explores the legal provisions for hacking as a cyber crime in Indonesia with a focus on the legal framework for hacking, criminal acts of hacking, and the challenges faced in dealing with changes and developments in cyber law. Indonesia's hacking legal framework, which primarily consists of the Information and Electronic Transactions Law (UU ITE), creates an important legal foundation for dealing with hacking. However, there are shortcomings in legal provisions that must be updated regularly to keep up with technological developments and increasingly sophisticated hacking tactics. This research aims to analyze the legal provisions that regulate hacking as a cyber crime in Indonesia. This includes an understanding of relevant legislation, the implementation of the law, as well as the obstacles faced in law enforcement related to hacking. This research uses normative legal research methods. By understanding the legal framework for hacking, criminal acts of hacking, and the challenges of changing cyber law in Indonesia, this research aims to provide deeper insight into how this country faces the threat of hacking in an increasingly complex digital era. With ongoing improvements in the legal framework, increased law enforcement capacity, and better public awareness, Indonesia can be more effective in protecting its society and digital infrastructure from the threat of cybercrime.